Generation of questions and answers for primary 6 mathematics : Part C - Lau, Dongcheng. (2012)
This project is to develop a web-based system to generate assessment questions and step-by-step solutions for a selected topic in Primary School or O-Level Mathematics. The system will also mark the answers submitted and analyze them to compute the performance, and identify the strengths and weaknesses. An option will also be provided to generate subsequent questions according to performance.